THE DEVELOPMENT OF INSTRUCTIONAL VIDEO ON SCIENCE SUBJECTS TO IMPROVE STUDENT ACHIEVEMENT AT SDN 3 BOLOREJO KAUMAN TULUNGAGUNG - Imra’atul - Mahmudah; Yulia Nugrahini, (INSPIRASI : JURNAL ILMU-ILMU SOSIAL, 2022)
AbstrackThe limitations of supporting media resulted in the student learning process not being optimal and not attracting students' attention. The strategy for using computers as teaching media is to develop a multimedia-based media and teaching materials. Microsoft Power Point is a software that will help compiling an effective, professional, and easy presentation. Microsoft Power Point will help an idea more interesting and clear when presented. So that researchers use the RnD method, according to Sugiyono (2011: 407) research and development is a research method used to produce certain products and test the effectiveness of these products. The development of interactive multimedia-based teaching materials produces products in the form of learning media using the macromedia flash professional 8 program which is accompanied by a Borg and Gall development design, namely: 1) researchers and data collection, 2) planning, 3) product draft development, 4) trial and improvement of the initial product, 5) revising the product, 6) field testing, 7) refinement of the product from the trial, 8) field implementation test, 9) final product refinement  10) dissimilation and implementation. The assessment carried out by design experts is 83%, it is suitable for use, while the percentage of content experts is 88%,  it is suitable for use by students. The percentage of learning experts is 90%, it means that it is feasible to be used in the learning process. From some of these validation experts, it means that this learning media does not need to be revised. This attractiveness was obtained from the results of the questionnaire assessment conducted by the experimental class group of fifth grade students at SDN 3 Bolorejo Tulungagung. Based on the percentage obtained by 92%, interactive multimedia-based learning media on understanding the concept of a simple plane is stated to be  interesting for research respondents because it has interesting animations.